CSC‐3436 sensitizes triple negative breast cancer cells to TRAIL‐induced apoptosis through ROS‐mediated p38/CHOP/death receptor 5 signaling pathways. Issue 12 (2nd October 2021) - Huang, Chun‐Chen; Cheng, Yi‐Ching; Lin, Ying‐Chao; Chou, Chun‐Hung; Ho, Chi‐Tang; Wang, Hao‐Kuang; Way, Tzong‐Der
Abstract: Tumor necrosis factor‐related apoptosis‐induced ligand (TRAIL) shows little or no toxicity in most normal cells and preferentially induces apoptosis in a variety of malignant cells. However, patients develop resistance to TRAIL, therefore, sensitizing agents that can sensitize the tumor cells to TRAIL‐mediated apoptosis are necessary. In this study, we investigated the effect of 2‐(3‐hydroxyphenyl)‐5‐methylnaphthyridin‐4‐one (CSC‐3436), an useful flavonoid, to overcome the TRAIL‐resistant triple negative breast cancer (TNBC) cells. We found that CSC‐3436 potentiated TRAIL‐induced apoptosis in TRAIL‐resistant TNBC cells and this correlated with the upregulation of death receptors (DR)‐5 and down‐regulation of decreased decoy receptor (DcR)‐1 expression. When examined for its mechanism, we found that the decreased expression of anti‐apoptotic proteins c‐FLIPS/L, Bcl‐Xl, Bcl‐2, Survivin, and XIAP. CSC‐3436 would increase the expression of Bax and promoted the cleavage of bid. In addition, the induction of DR5 by CSC‐3436 was found to be dependent on the modulation of reactive oxygen species (ROS)/p38/C/EBP‐homologous protein (CHOP) signaling pathways. Overall, our results indicated that CSC‐3436 could potentiate the apoptotic effects of TRAIL through down‐regulation of cell survival proteins and upregulation of DR5 via the ROS‐mediated upregulation of CHOP protein.